Commercial Aircraft Composite Technology - Breuer, Ulf Paul.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is based on lectures held at the faculty of mechanical engineering at the Technical University of Kaiserslautern. The focus is on the central theme of societies overall aircraft requirements to specific material requirements and highlights the most important advantages and challenges of carbon fiber reinforced plastics (CFRP) compared to conventional materials. As it is fundamental to decide on the right material at the right place early on the main activities and milestones of the development and certification process and the systematic of defining clear requirements are discussed. The process of material qualification - verifying material requirements is explained in detail. All state-of-the-art composite manufacturing technologies are described, including changes and complemented by examples, and their improvement potential for future applications is discussed. Tangible case studies of high lift and wing structures emphasize the specific advantages and challenges of composite technology. Finally, latest R&D results are discussed, providing possible future solutions for key challenges such as low cost high performance materials, electrical function integration and morphing structures.
Introduction -- Requirements, development and certification process -- Material technology -- Manufacturing technology -- Testing -- Repair -- Flap design studies -- Tailored wing design -- New developments.
Keywords: Aerospace engineering; Astronautics; Building materials; Aerospace Technology and Astronautics; Structural Materials